Informatics - Editor, Editor (Journal of Engineering Education Transformations, 1993)
Central Govt. Plans Training 5 Lakhs Youths The central Govt. has decided to train five lakh youths in the next five years and provide them technical skills in various areas. This technology mission scheme would cover diverse fields like poultry, gem cutting, sophisticated electronic assembly.